2009
DOI: 10.1080/01443410903103657
|View full text |Cite
|
Sign up to set email alerts
|

Real books vs reading schemes: a new perspective from instructional psychology

Abstract: A fiercely contested debate in teaching reading concerns the respective roles and merits of reading schemes and real books. Underpinning the controversy are different philosophies and beliefs about how children learn to read. However, to some extent debates have largely been rhetoric-driven, rather than research-driven. This article provides a theoretical perspective derived from instructional psychology and explores the assumptions that have been made about the use of real books and reading schemes, which hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 49 publications
2
48
1
Order By: Relevance
“…real books or graded reading books: for further discussion on both issues, see Reynolds et al, 2010;Solity & Vousden, 2009). Hence, several reviews of the research evidence recommend a structured programme of phonics (gpc knowledge) should be the main emphasis of an early intervention programme for struggling readers.…”
Section: Contentmentioning
confidence: 99%
“…real books or graded reading books: for further discussion on both issues, see Reynolds et al, 2010;Solity & Vousden, 2009). Hence, several reviews of the research evidence recommend a structured programme of phonics (gpc knowledge) should be the main emphasis of an early intervention programme for struggling readers.…”
Section: Contentmentioning
confidence: 99%
“…Snow, Burns and Griffin (1998) support the inclusion of sight words, stating that instruction in first grade should include ''sight recognition of frequent words' ' (p. 194). Solity and Vousden (2009) recently suggested that if students are taught a bank of crucial high-frequency words in a program that features instruction in key phonic skills, they will be able to read approximately 90% of monosyllabic words they encounter in text. Although there are differences of opinion about the number of sight words that should be taught, evidence from an analysis of texts by Solity and Vousden indicates that the 100 words that occur most frequently should be taught and that, beyond this, other words occur so infrequently that there is little reason for teaching them.…”
Section: What Elements/activities Should Be Included?mentioning
confidence: 99%
“…As choosing texts that link to the sequence of phonics skills in the instructional program and are 80-90% decodable can be difficult and time-consuming, program designers also need to consider the type of books they select from: whether they have been designed as texts for reading schemes or whether they are ''real'' books. Solity and Vousden (2009) analysed books available for use with beginning readers and found little difference in the number of core high frequency words and letter-sound correspondences that are encountered by students in real books compared to texts from reading schemes. This led them to suggest that ''the debate may be resolved by teaching an optimal level of core phonological, phonic, and sight vocabulary skills, rigorously and systematically in conjunction with the use of real books'' (p. 503).…”
mentioning
confidence: 98%
“…Overall, pronunciation is better predicted by the application of onset and rime sized correspondences than by the application of grapheme-phoneme correspondences (Vousden, 2008), but many more onset-rime units are required to achieve accurate pronunciation (Solity & Vousden, 2009;Vousden, 2008), thereby increasing the complexity of the solution to be adopted by the cognitive system, an issue that has received little consideration. For example, Solity and Vousden (2009) showed that the amount of monosyllabic adult text that could be accurately decoded by applying 64 grapheme-phoneme correspondences would require the application of 63 onset and 471 rime correspondences. Following the literature that found a developmental progression from large to small unit phonological awareness, and a number of studies that suggested training children about onset and rime could be beneficial for reading acquisition (Goswami, 1986;Wise, Olson, & Treiman, 1990), there emerged a large literature comparing different methods of instruction based on different unit sizes, from whole words (e.g., I. S. Brown & Felton, 1990) and rimes (e.g., Greaney, Tunmer, & Chapman, 1997), to graphemes (e.g., Stuart, 1999).…”
Section: The Simplicity Principlementioning
confidence: 99%